A public health perspective on the responsibility of mass media for the outcome of the anti-COVID-19 vaccination campaign: the AstraZeneca case - Bianchi, F. P.; Tafuri, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
On February 9, 2021, the Italian Ministry of Health made the “Covid-19 vaccine AstraZeneca” (now “Vaxzevria”) available for use in the anti-COVID-19 vaccination campaign. However, in early March, the media reported that five people died a few days after receiving the vaccine. The reaction among both those already vaccinated and the vaccine candidates was one of near panic. The subsequent events have had long-lasting consequences, as 10–20% of vaccine candidates have since refused vaccination with the AstraZeneca vaccine, so in addition to the delay in vaccination, ~200,000 doses of it were not administered.The goal of the vaccination campaign in Italy, when operating at full capacity, was to administer 500,000 doses per day, for a total of 3,500,000 doses per week. In this large amount of people, it is statistically certain that a certain number of subjects will develop non-vaccine related health problems or even die from causes unrelated to having been vaccinated. At this time in history, press reports must be inspired by a strong sense of responsibility and awareness of the potential consequences of misinformation; this is particularly true, especially because also the social media get inevitably involved.